Impact of early postoperative platelet count on volumetric liver gain and perioperative outcomes after major liver resection. Issue 7 (9th March 2016) - Margonis, G. A.; Amini, N.; Buettner, S.; Besharati, S.; Kim, Y.; Sobhani, F.; Kamel, I. R.; Pawlik, T. M.
Abstract: Background: Although perioperative platelet count has been associated with postoperative morbidity and mortality, its impact on liver regeneration has not been examined directly. This study sought to determine the impact of platelet count on liver regeneration after major liver resection using cross‐sectional imaging volumetric assessment. Methods: Patients who underwent major liver resection between 2004 and 2015 and had available data on immediate postoperative platelet count, as well as preoperative and postoperative CT images, were identified retrospectively. Resected liver volume was subtracted from total liver volume (TLV) to define postoperative remnant liver volume (RLVp ). The liver regeneration index was defined as the relative increase in liver volume within 2 months ((RLV2m  – RLVp )/RLVp, where RLV2m is the remnant liver volume around 2 months after surgery). The association between platelet count, liver regeneration and outcomes was assessed. Results: A total of 99 patients met the inclusion criteria. Overall, 25 patients (25 per cent) had a low platelet count (less than 150 × 10 9 /l), whereas 74 had a normal–high platelet count (at least 150 × 10 9 /l). Despite having comparable clinicopathological characteristics and RLVp /TLV at surgery ( P  = 0·903), the relative increase in liver volume within 2 months was considerably lower in the low‐platelet group (3·9 versus 16·5 per cent; P  = 0·043). Patients with a low platelet count had an increased risk of postoperative complications (72 versus 38 per cent; P  = 0·003), longer hospital stay (8 versus 6 days; P  = 0·004) and worse median overall survival (24·5 versus 67·3 months; P  = 0·005) than those with a normal or high platelet count. Conclusion: After major liver resection, a low postoperative platelet count was associated with inhibited liver regeneration, as well as worse short‐ and long‐term outcomes. Immediate postoperative platelet count may be an early indicator to identify patients at increased risk of worse outcomes. Abstract : Platelet count counts